2022
DOI: 10.1007/s11214-022-00900-8
|View full text |Cite
|
Sign up to set email alerts
|

The Early History of Heliospheric Science and the Spacecraft That Made It Possible

Abstract: Our understanding of the interaction of the large-scale heliosphere with the local interstellar medium (LISM) has undergone a profound change since the very earliest analyses of the problem. In part, the revisions have been a consequence of ever-improving and widening observational results, especially those that identified the entrance of interstellar material and gas into the heliosphere. Accompanying these observations was the identification of the basic underlying physics of how neutral interstellar gas and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 197 publications
(359 reference statements)
0
7
0
Order By: Relevance
“…The models of the heliospheric magnetic fields in the solar wind were widely discussed (see e.g. Axford 1972;Zank et al 2022, and the references therein) and see Herbst et al (2022) for a recent review of models of stellar astrospheres. In particular, it was shown by Axford (1972) and Cranfill (1974) that in nearly incompressible subsonic flow downstream of the spherical wind termination shock the azimuthal magnetic field 𝐵 𝜙 would increase as ∝ 𝑟 up to the magnitude which is dynamically significant to affect the plasma flow.…”
Section: Magnetic Field Amplification In the Cluster Corementioning
confidence: 99%
“…The models of the heliospheric magnetic fields in the solar wind were widely discussed (see e.g. Axford 1972;Zank et al 2022, and the references therein) and see Herbst et al (2022) for a recent review of models of stellar astrospheres. In particular, it was shown by Axford (1972) and Cranfill (1974) that in nearly incompressible subsonic flow downstream of the spherical wind termination shock the azimuthal magnetic field 𝐵 𝜙 would increase as ∝ 𝑟 up to the magnitude which is dynamically significant to affect the plasma flow.…”
Section: Magnetic Field Amplification In the Cluster Corementioning
confidence: 99%
“…[15], but a proper treatment of the Spreiter number would permit this to be tightened, while keeping in mind that there are several additional factors that modify ram pressure stripping such as the effects of extended gas [17,18]. Thirdly, there are important astronomical applications for which the Mach number is close to unity, including shocks in the very local interstellar medium (VLISM) [19,20], in which case momentum flux overestimates ram pressure by false(1Spfalse)/Sp50normal% (figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…H atoms resonantly scatter Lyman‐α photons. IPH properties have therefore been examined using Lyman‐α emissions observed by multiple spacecraft from various points in the solar system (e.g., Baliukin et al., 2022; Galli et al., 2022; Zank et al., 2022) It is found that the IPH flow direction emanates from close to the heliospheric “nose” with no significant variation of the IPH flow longitude over time (Lallement et al., 2005; Koutroumpa et al., 2017). The IPH velocity ranges between 18 ± 2 km/s and 25.7 ± 2 km/s, and varies with solar activity, line of sight, and distance from the Sun (Vincent et al., 2011).…”
Section: Introductionmentioning
confidence: 99%